Technical match actions and plasma stress markers in elite female football players during an official FIFA tournament - Póvoas, S.; Ascensão, A.; Magalhães, J.; Silva, P.; Wiig, H.; Raastad, T.; Castagna, C.; Andersson, H. (Scandinavian Journal of Medicine & Science in Sports, 2022)
This study analyzed the impact of performing four consecutive football matches separated by 48-72 hours during a FIFA tournament on physical load, technical performance and plasma markers of redox state, muscle damage and inflammation in elite female players. Forty-eight players from three national teams were evaluated at seven time points: before (baseline) and throughout the tournament (after each match and before two training sessions). Only data from players who played all matches were included in the analyses (N = 13). The players were divided into high-rank (N = 6) and low-rank (N = 7) team players according to FIFA standards. Plasma creatine kinase (CK), C-reactive protein (CRP), total antioxidant status (TAS), and uric acid (UA) were analyzed at the selected time points. Technical performance and physical load were also quantified according to team rank. Players from low-rank teams played significantly more time than high-rank players (85 ± 10 vs 67 ± 15 minutes; P = .02; d = 1.51). Low-rank team players presented higher values in technical performance actions than the high-rank team players, but most of the differences were explained by the longer match time played. UA content differed across the matches, increasing from baseline (F(4,40) = 3.90; P = .01) and more in the high-rank team players (F(1,10) = 20.46; P = .001), while CRP only differed across the matches (F(4,36) = 2.66; P = .05), also increasing from baseline. A large time effect was shown for UA only in the high-rank players (n2p = 0.50; P = .02). Four consecutive matches did not result in considerable alterations in plasma stress markers, physical load, and technical performance in elite female football players from distinct rank levels.